Multiple sclerosis impact on pregnancy: An update on management issues: - Jafarinia, Morteza; Badali, Ahmadreza; GhorbaniNia, Rahil; Mohammadian, Shima; poudineh, Sahar; Sarlak, Alireza; Eghbali, Mohammadreza; Behzadi, Esmaeil (Galen Medical Journal, 2022)
Women with multiple sclerosis (MS) of reproductive age are becoming pregnant at an alarmingly high rate. Disease control is required during the preconception, prenatal, and postpartum periods to reduce the likelihood of relapses of MS while minimizing hazards to the mother and fetus. It has long been understood that the disease activity of MS noticeably decreases in the third trimester of pregnancy, then noticeably increases in the first three months after delivery before returning to its pre-pregnancy baseline. Relapse during pregnancy and high rates of relapse before becoming pregnant have both been linked to an increased risk of postpartum attacks. In patients with relapse MS, recent results continue to support the notion that pregnancy does not affect long-term disease progression (and may even have the opposite effect); the situation is less clear for patients with progressive MS. It is comforting to know that none of the MS disease-modifying medications have been shown to cause teratogenic consequences. This review discusses the effects of pregnancy on disease activity and how to handle relapses when pregnant and breastfeeding.